The Evolution of Ransomware: Tactics, Techniques, and Mitigation Strategies - Nagar, Gourav (International Journal of Scientific Research and Management (IJSRM), 2024)
Ransomware has developed into one of the most dangerous cyber threats. It is developed for the purpose of encrypting the data, and the owner is to pay the specified amount of money for the decoder. From simple rudimentary to developed sort with advanced encryption methods and modern distribution techniques, this research article is a complete historical journey of ransomware. Some of the specific aspects of ransomware development include the process of how the attackers act, starting from the traditional approach of spraying the malware to another strategic approach of singling out industries and organizations for attacks.The article also analyzes how the world came to know about ransomware-as-a-service (RaaS). The analysts have attributed the docket to the fact that it has also made it easy for inexperienced and unskilled hackers to embrace the commodity space by merely launching ransomware attacks. Current ransomware strategies that hackers employ include double extortion, where they steal information and threaten to publish the stolen data publicly, besides demanding a ransom for the encrypted information. The use of coins in the payment of ransom is examined with regard to their anonymity and the emergence of targeting of key infrastructure and other giant entities.Tactics that can allow for minimizing the attacks’ impact are equally crucial in the fight against ransomware. Some of the extensive strategies highlighted in this article are basic cyber hygiene measures, backup and restore methodologies, and endpoint detection and prevention measures. Implementing frequent training exercises to sensitize users to the risks of ransomware attacks is underlined, as is the need to have a clearly outlined incident response procedure in case of infections to enable the speedy handling of the attacks.This paper argues that an ability to comprehend the complexity of today’s ransomware, along with multiple layers of a defense system, will help organizations improve their readiness against this adaptive and continuous threat. This paper contains an analysis of the current state of ransomware and measures that need to be taken to curb the threat posed by this cyber threat; thus, it can serve as a valuable resource to cybersecurity experts.